Formulación de una cerveza artesanal de fermentación alta tipo special beer utilizando adjuntos provenientes del departamento del Choco (2023)
This project proposes a formulation of high-fermentation craft beer, special beer type, implementing raw materials such as borojó, rice and sugar cane from the department of Chocó located in the Colombian Pacific region. Furthermore, the implementation of these inputs will be established from a preliminary investigation where the base recipe and the addition of said adjuncts in the production stage will be determined. On the other hand, the formulation of the ideal concentrations was carried out experimentally in the Merak brewery, to obtain a product with physicochemical, organoleptic and microbiological characteristics that meet the required quality standards. For this, the degrees of alcohol (volume/volume percentage), pH, color (EBC), density and IBU degrees of the final product were determined. On the other hand, through the use of Petrifilm 3M® tests, microbiological tests were carried out on the final product, ensuring the quality and safety of the beer to define that the combination of borojó and rice with the best characteristics is 15% rice and 1000g of borojó . Finally, through a cost analysis, the cost of the beer was determined.